IMPLEMENTATION OF VIRTUAL AND AUGMENTED REALITY TECHNOLOGIES IN THE EDUCATIONAL PROCESS IN THE TRAINING STUDENTS IN THE FIELD OF KNOWLEDGE OF «ARCHITECTURE AND CONSTRUCTION» (Innovative professional education, 2024)
In order to form the cognitive independence of the students of education, in accordance with the needs of informatization of education and computerization of education, there is a need to modernize the content and goals of professional training of teachers, in particular, the formation of computer literacy, namely: knowledge of the basic concepts of informatics and computer technology; methods of functioning and use of virtual and augmented reality tools, methods of organizing work in the e-learning system, methods of searching, processing and using information in the space of virtual and augmented reality.
Keywords: Augmented reality (AR), virtual reality (VR), reference token, conceptual space